Pemanfaatan Biopori Sebagai Upaya Mitigasi Bencana Banjir di Nagari Pangkalan, Kecamatan X Koto Pangkalan Kabupaten Lima Puluh Kota - Lailatur Rahmi; Azhari Syarief (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2020)
This activity aims to make a disaster prone Nagari district base of the subdistrict of the regency of fifty cities, became the Nagari alert disaster, so the community Nagari the base is tough and standby if there is suddenly a flood disaster, so the impact is not too big. The lack of knowledge and public awareness of flood disaster and environmental concern, as a result of prioritizing economic interests, so that many communities do land clearing and reduced green open land in the base area. In fact, with the clearing of land that is not balanced with environmental conditions, then there is rain with great intensity, then the area becomes a region that is prone to flood disaster. It is proven two years in a row (2016 and 2017) flooding occurs that exceeds 1 meter so it has a big impact on all the facilities and infrastructure including agriculture and plantation owned by Nagari Pangkalan community. Some approach methods offered to support the realization of this dedication program are training and demonstration with the descriptions, among others: (1) Case studies, (2) practice/demonstration primarily in the study of Biopori, (3) Brains Storming/Community Ideas Gathering, (4) questions and answers between community and instructors or related governments, (5) lectures that contain core material and advanced activities plan that is a solution to the problems faced by the community. This activity is expected to be in accordance with the plan of activity and can be measured in order: (1) assisting the community in improving their knowledge and skills in utilizing biopolar as one of the efforts to overcome flooding, (2) assisting local governments in an effort to improve community knowledge and skills through the transfer of knowledge and skills so as to anticipate flood disaster and to remind the welfare of